Firebrand Generation From Thermally-Degraded Cylindrical Wooden Dowels - Caton-Kerr, Sara E.; Tohidi, Ali; Gollner, Michael J. (Frontiers in Mechanical Engineering, 2019)
During wildland fires, firebrands form once they break off of burning vegetation or structures. Many are then lofted into the fire plume where they are transported long distances ahead of the fire front, igniting new “spot” fires as they land. To date, very few studies have been conducted on the breakage mechanism of thermally-degraded vegetative elements. Knowledge of these mechanisms is needed to feed mathematical models of firebrand transport from traditional wildfires as well as those that spread into communities. First, a framework to understand the behavior of thermally-degraded wooden elements under simultaneous external loading is presented. A set of experiments were designed such that cylindrical wooden dowels of different species are exposed to different heating conditions similar to wildland fires, in order to model the breakage mechanisms of these elements in the absence of wind. The thermally-degraded elements are subjected to the three-point bending test to obtain the mechanical response of the materials after combustion. Assuming Hookean Orthotropic behavior for combusted dowels, dimensional analysis of the results reveals that the ultimate strength of the dowels is affected by the recoverable elastic strain during loading, which is found to occur under two distinct regimes. These results are not only important for better understanding of the breakage mechanisms but also are advantageous for developing a failure theory of thermally degrading wooden elements under simultaneous wind loading conditions.